Design of Therapeutic Digital Games that Support Dialogue with Children about Death - Verhalen, Aline Elias Cardoso; Rodrigues, Kamila Rios Da Hora (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Grief and loss are topics that people generally avoid discussing, especially with children. The pandemic caused by COVID-19 caused thousands of children to lose relatives or friends, and this topic gained notoriety and relevance. Parents and caregivers needed to discuss death and grief with children to they understand what was happening worldwide. However, this is still a subject full of taboos. The literature highlights the importance of talking to children about their emotions during a loss and how to deal with them so that there are no traumas in adult life. This master’s project presents the design of two serious games designed to help health professionals during (1) grief therapies with children and (2) discussions about finitude with this same public. The games were created using the SemTh methodological approach, which supports therapeutic digital game design and evaluation activities. The construction of the games was supported by a multidisciplinary team, including Health Professionals (psychologists and occupational therapists) and Computing professionals. The designed games were materialized on the RUFUS platform (from the research group of these authors), which allows the authoring of digital games from predefined templates (game mechanics). With the activities of this master’s project, two new templates were inserted in the platform: narrative and inverse narrative, which allows the construction of games through stories. Empirical and analytical studies were conducted to evaluate the usability of games and templates on the RUFUS platform.